The sacred serpent: a journey to the roots of Medicine - Zevallos, Antonia N.; Borroto , Eugenio R. (Revista Gregoriana de Ciencias de la Salud, 2024)
History is shaped by the winners and those in power, using symbolic elements crucial to collective identity. In medicine, symbols such as the rod of Asclepius and the caduceus of Mercury, often misinterpreted, are universally recognized. This essay aims to analyze the origin and evolution of the staff of Asclepius and the caduceus of Mercury, delving into their meaning and influence on the formation of medical professions. It explores how each symbol, with its mythological roots and cultural representations, has impacted the perception and development of medicine over time, as well as the importance of maintaining historical and cultural accuracy in the contemporary use of these symbols.